2002
DOI: 10.1128/iai.70.8.4247-4253.2002
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4Induces Nitric Oxide Synthesis inTrypanosoma cruzi-Infected Murine Macrophages and Mediates Resistance to Infection

Abstract: . Finally, daily treatment of infected mice with CP-105,696 was accompanied by a significantly higher level of blood parasitemia, but not lethality, than that seen in vehicle-treated animals. In conclusion, our results suggest a role for LTB 4 during experimental T. cruzi infection. Chemoattractant molecules such as LTB 4 not only may play a major role in leukocyte migration into sites of inflammation in vivo but also, in the event of an infection, may play a relevant role in the activation of recruited leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
66
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 31 publications
10
66
0
3
Order By: Relevance
“…Moreover, treatment of macrophages with LTB 4 induces iNOS expression and NO production in both strains of mice. Our results are in line with the findings of Talvani et al (14) that showed a synergism between infection with T. cruzi and treatment with LTB 4 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, treatment of macrophages with LTB 4 induces iNOS expression and NO production in both strains of mice. Our results are in line with the findings of Talvani et al (14) that showed a synergism between infection with T. cruzi and treatment with LTB 4 .…”
Section: Discussionsupporting
confidence: 83%
“…However, some persistent leishmanicidal activities of LTB 4 -treated macrophages even in the presence of L-NAME suggest that other mechanisms independent of NO may be operative. Talvani et al (14) demonstrated that NO is the molecule involved 6 stationary phase promastigotes of L. amazonensis in the left hind footpad at time 0, and were treated or not from days 1-7 with the 5-LO inhibitor zileuton (1 mg/kg i.p. daily).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown the involvement of 5-LO during murine Chagas' disease. Literature data show that LTB 4 leads to an increase in NO synthesis, which participates in the resistance to the infection (41). However, Clark and coworkers (36) demonstrated in vivo that 5-LO KO mice have increased NO and IL-6 levels in plasma with a concomitant decrease in the expression of iNOS in cardiac tissue 12 d postinfection with T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
“…In such mice, infection with all of the aforementioned pathogens was facilitated by the absence of TLR9. LTB 4 has also shown antimicrobial activities against Klebsiella pneumoniae (42), Trypanosoma cruzi (43), and Leishmania amazonensis (44). Moreover, we previously demonstrated the antiviral properties of LTB 4 against different viruses such as human and murine CMV and HSV-1 as well as the influenza virus (20 -22).…”
Section: Discussionmentioning
confidence: 99%